Dynamics of poverty-related dissimilarities in fertility in Nigeria: 2003-2018 (2020)
Nigeria is one of the high fertility countries worldwide. Little is known about the differences in fertility experience of women in poor and rich households in Nigeria. We ex amined the relationship between household wealth and fertility in Nigeria with focus on women from poor and rich households.This national representative and cross-sectional design study involved analysis of fourrounds (2003, 2008, 2013, 2018) of Nigeria Demographic Health and Survey data . Theoutcome variable was fertility measured from the full birth history information reported by women of reproductive age. Data were analyzed using descriptive statistics, direct and Gompertz-relational demographic methods, logistic regression and negative binomial re gression models (α=0.05). Across the survey years, the mean number of children ever born (CEB), the total fer tility rate and the percentage of women who had high fertility were consistently higher among the women from poor households than those from the rich households. From 2003 to 2018, declining pattern (slope = -0.87) in percentage of high fertility women was observed among rich unlike the poor women (slope = +0.31) where a slight increase was observed. In 2018 as for other survey rounds, about 18.7% and 38.4% of rich and poor women had high fertility (CEB≥5) respectively. The likelihood of high fertility (CEB≥5) was 2.74 (C.I=2.60-2.89, p<0.001) times higher among poor women than the rich women. In 2018,the fertility incidence risk ratio was about 8.0% higher among the women from the poo rhouseholds than their counterparts from the rich households and this pattern was observed when some other factors were included in the regression model across the survey years (2003-2018).